Natural Plant Compounds: Does Caffeine, Dipotassium Glycyrrhizinate, Curcumin, and Euphol Play Roles as Antitumoral Compounds in Glioblastoma Cell Lines? - Bonafé, Gabriel Alves; Boschiero, Matheus Negri; Sodré, André Rodrigues; Ziegler, Jussara Vaz; Rocha, Thalita; Ortega, Manoela Marques (Frontiers in Neurology, 2022)
Many plant-derived compounds are shown to be promising anti-tumor therapeutic agents by enhancing apoptosis-related pathways and cell cycle impairment in tumor cells, including glioblastoma (GBM) cell lines. We aimed to review four natural plant compounds effective in GBM cell lines as caffeine, dipotassium glycyrrhizinate (DPG), curcumin, and euphol. Furthermore, anti-tumoral effect of these plant compounds on GBM cell lines through microRNAs (miRs) modulation was investigated. However, only DPG and curcumin were found as effective on miRs modulation. Caffeine arrests GBM cells cycle in G0/G1 phase by cyclin-dependent-kinases complexes inhibition and by decreasing BCL-2 and increasing FOXO1 expression levels causing greater apoptotic activity. Caffeine can also directly inhibit IP3R3, p38 phosphorylation, and rho-associated-protein-kinase (ROCK), decreasing cell invasion and migration capacity or indirectly by inhibiting the tissue-inhibitor-metalloproteinase-1 (TIMP-1) and integrins-β1 and -β3, leading to lower matrix metalloproteinases (MMP)-2 and MMP-9. DPG presents anti-tumoral effect in GBM cells related to nuclear factor kappa B (NF-κB) pathway suppression by IRAK2 and TRAF6-mediating miR-16 and miR-146a, respectively. More recently, it was observed that DPG up-regulated miR-4443 and miR-3620, responsible for post-transcriptional inhibition of the NF-κB pathway by CD209 and TNC modulation, respectively leading to lower MMP-9 and migration capacity. Curcumin is able to increase miR-223-3p, miR-133a-3p, miR-181a-5p, miR-34a-5p, miR-30c-5p, and miR-1290 expression leading to serine/threonine kinase (AKT) pathway impairment and also it decreases miR-27a-5p, miR-221-3p, miR-21-5p, miR-125b-5p, and miR-151-3p expression causing p53-BCL2 pathway inhibition and consequently, cellular apoptosis. Interestingly, lower expression of miR-27a by curcumin action, enhanced the C/EBP homologous protein (CHOP) expression, leading to paraptosis. Curcumin can inhibit miR-21 expression and consequently activate apoptosis through caspase-3 and death receptor (DR)-4 and -5 activation. Autophagy is controlled by the LC-3 protein that interacts with Atg family for the LC3-II formation and autophagy activation. Euphol can enhance LC3-II levels directly in GBM cells or inhibits tumor invasion and migration through PDK1 modulation.